2022
DOI: 10.3390/jcm11164710
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic Chemotherapy for Metastatic Breast Cancer Treatment: Clinical and Preclinical Data between Lights and Shadows

Abstract: Metronomic chemotherapy (mCHT), defined as continuous administration of low-dose chemotherapeutic agents with no or short regular treatment-free intervals, was first introduced to the clinic in international guidelines in 2017, and, since then, has become one of the available strategies for the treatment of advanced breast cancer (ABC). Despite recent successes, many unsolved practical and theoretical issues remain to be addressed. The present review aims to identify the “lights and shadows” of mCHT in preclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…Taken together with other published data, our results confirm the multimodality mechanism of action of mCHT and contribute to understanding of the cellular and molecular mechanisms underlying the effect observed in clinical trials in TNBC patients treated with mCHT therapy ( 69 ). Moreover, our findings support the rationale for its employment in TNBC patients, where the dual targeting of the tumor and its vasculature at the same time would result in better therapeutic outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…Taken together with other published data, our results confirm the multimodality mechanism of action of mCHT and contribute to understanding of the cellular and molecular mechanisms underlying the effect observed in clinical trials in TNBC patients treated with mCHT therapy ( 69 ). Moreover, our findings support the rationale for its employment in TNBC patients, where the dual targeting of the tumor and its vasculature at the same time would result in better therapeutic outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…Metronomic VEX’s safety profile in METEORA-II was similar to that of other metronomic regimens in MBC and still manageable . Another important aspect is the cost of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Low‐dose continuous administration of CAP is also safe and well‐tolerated 26,46–48 . The combination of oral VNR and CAP has been studied in several clinical trials 49–51 . A phase II clinical trial revealed that the metronomic combination regimen encompassing VNR, cyclophosphamide and CAP displayed remarkable activity and favorable tolerability in patients with HR‐positive MBC.…”
Section: Discussionmentioning
confidence: 99%
“…Another open‐label, international, multicenter, phase II study enrolled 40 MBC cases who were administered oral VNR at 60 mg/m (2) on days 1, 8 and 15, along with CAP at 1000 mg/m (2) bid from day 1 to day 14. The treatment cycles were 3 weeks, and the response rate was 23.5% in the 34 evaluable cases 50 . The VICTOR‐2 study examined the efficacy of the mNC regimen in patients with HER‐2‐negative MBC.…”
Section: Discussionmentioning
confidence: 99%